IMPLIKASI PERANG SIBER ANTARA ISRAEL, AMERIKA SERIKAT DAN IRAN MELALUI OLIMPIC GAME OPERATION TERHADAP FASILITAS PROGRAM NUKLIR IRAN PADA PERIODE PEMERINTAHAN MAHMOUD AHMADINEJAD: PERANG SIBER STUXNET 2010 - Ayunita Harianja; Adi Rio Arianto; M. Chairil Akbar Setia (Moestopo Journal of International Relations, 2022)
Iran's nuclear program is the most collaborative in the Middle East region. International criticism regarding the development of the program did not make Ahmadinejad to stop the nuclear program in Iran. The United States decided to take action regarding Iran's nuclear program by cooperating with Israel to carry out attacks on nuclear facilities Israel is located in the Natan region. This attack is known as the Olympic Game Operation with the code "olympics, by creating a dangerous malware virus called Stuxnet, designed with the aim of taking over control over remote industrial systems. This attack is expected to be capable of nuclear facilities in the Natanz region as a whole, but in reality, this attack was only able to have a short-term impact on the damage caused. This study aims to find out how the impact of cyber war involving Israel, the United States, and Iran on Iranian power in the Middle East region. The author uses 3 frameworks of thought in this research, namely International Security, Cyber War, and Cyber Attacks. In this study, the author uses 2 data sources, namely primary data and secondary data. Iran's nuclear facilities are able to have both short and long-term impacts in several fields and are able to influence the position of Iran's power in the Middle East region.Keywords : Nuclear, Stuxnet Virus, International Security, Cyber War, Cyber Crime, Olympic Game Operation